ANALISIS PERLAKUAN AKUNTANSI ATAS PENDAPATAN DAN BIAYA PADA PT.SKYTECH INDONESIA - Goni, Lesli Mersi; Tinangon, Jantje J.; Walandouw, Stanley Kho (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Income is one of the important elements to maximize the profits. Revenue should be measured appropriately so that the revenue will be recognized the right company , so avoid overstate or understate the presentation of the financial statements . According to PSAK No. . 34 ( revised 2010 ) , there are two methods of revenue recognition method used is the percentage of completion and completed contract method . The purpose of this study was to determine the suitability of the recognition of revenue and expenses by PT . Skytech Indonesia with PSAK No. 34 ( revised 2010 ) . The analytical method used is descriptive qualitative , where the data obtained , compiled , categorized , interpreted , and analyzed so as to give a proper picture . The results of the study revealed that the company uses the percentage of completion method on the basis of cost against the cost of which has shown a reasonable value . Similarly, the recognition and measurement of costs associated with the revenue based on the fair value .